A new empirical model to predict stress intensity factor for double interacting surface cracks located in hollow cylinder - Fakhri, Omar Mohammed (2021)
Fracture in cylinders is one of the most popular types of failure. Owing to the impact of production processes, nondestructive testing, and severe operational conditions, etc., cracks exist. The cracks could be detected in single or multiple form, where multiple cracks considered among the significant concerns that cylinders expected to experience. This is because in the existence of multiple neighboring cracks, crack interaction can take place between cracks and accelerates fracture process and lead to a catastrophic failure. Consequently, this study focuses on the problem of double interacting surface cracks located on external and internal surfaces of a hollow cylinder and oriented into parallel and non-coplanar parallel cracks configuration. Stress Intensity Factor (SIFs) has been chosen as the driving force to define the crack interaction. The SIFs have been analyzed for a wide variety of crack geometry, and cylinder type as well as separation distances utilizing finite element software Ansys under different types of mechanical loadings. Based on the analysis results, an empirical mathematical model was produced to predict the SIFs for double parallel cracks using the SIFs for a single crack, for thick and thin cylinders, separately. The empirical model was verified in terms of performance evaluation metrics, which exhibited prediction error less than 5%. Also, it is shown that crack interaction influence for parallel cracks demonstrated by shielding interaction influence only, while both shielding, and amplification impacts produced for non-coplanar cracks. The crack separation distance (horizontal and angular) between the cracks displayed substantial influence on interaction since it exhibited the ability to convert the interaction behavior from shielding to amplification impact (for angular). The presented results in this research serve the literature database since SIFs for a wide variety of cracks geometry have been introduced under different types of loading. Besides, the proposed mathematical model could be used easily and confidently as it displayed a high rate of accuracy.